Laser-induced bubble generation on a gold nanoparticle: A nonsymmetrical description - Acosta, Eduardo (2015)
The modeling of bubbles initiated by laser-irradiated nanoparticles is of interest for many applications. There is at present no comprehensive physical picture for all the stages of the process. We present an alternative approach with a key assumption: the vapor bubble evolves adjacent to the nanoparticle. To take into account the irreversible evolution, the statistical rate theory was used, thus avoiding the introduction of extra ad hoc parameters. Model results agree well with published data and our measurements. The only free parameter, the thermal boundary conductance, can be obtained by adjusting the model to the experimental data.